A kinematic analysis on the immediate effects of occlusal splints in gait and running body sway patterns - Dias, Amândio; Redinha, Luís; Rodrigues, Maria João; Silva, Luís; Pezarat-Correia, Pedro (Cranio, 2022)
: This study aims to determine whether changes in dental occlusion are correlated to body posture during walking and running. : Fifteen healthy subjects were assessed by a prosthodontist and deemed asymptomatic. Analyses of gait and running were performed in three conditions, in random order: a) occlusal splint; b) placebo splint; and c) no splint. The occlusal splint used in this study positioned the mandible in a stable position. Kinematic data was collected using a 3D motion capture system. : Changes in dental occlusion induced by occlusal splints did not influence body sway during gait or running. No significant differences were found between any of the test conditions. : Occlusal splints have no effect on body sway during gait or running. High inter-subject variability in kinematic parameters was found, which should be considered in future studies.